The challenges of ethical behaviors for drug supply in pharmacies in Iran by a principle-based approach - Mahla Iranmanesh; Vahid Yazdi-Feyzabadi; Mohammad Hossein Mehrolhassani (BMC Medical Ethics, 2020)
Abstract Background Pharmacists as the trustee of pharmacy services must adhere to ethical principles and evaluate their professionalism. Pharmacists may sometimes show different unethical behaviors in their interactions, so it is essential to understand these behaviors. The present study aimed to determine the challenges of ethical behaviors based on a principles-based approach in the area of drug supply in pharmacies. Methods This qualitative content analysis was conducted in Kerman in 2018. A number of key players in the field of medication supply were selected using snowball sampling to interview. An effort was made to select samples with maximum variation. Exclusion criteria include having less than 3 years of work experience in pharmacy and supervision, not willing to participate in the interview, and not participating in the interview for 3 times. The participants in this study consisted of pharmacy technicians (n = 5), patients (n = 6), pharmacists (n = 8), inspectors of insurance companies (n = 4), and inspectors of food and drug administration (n = 3). Data were analyzed using directed content analysis by Maxqda software version 10 (VERBI Software, Berlin, Germany). The principles of “Beauchamp and Childress Ethics” theory including autonomy, beneficence, non-maleficence, and justice were selected as the main principles. Results After data analysis, 8 main categories and 26 subcategories were obtained. The main categories include patient privacy, patient independence, communication principles, patient-centered services, drug supplier, patient harm avoidance, supervision, and distributive, procedural, and interactional justice. The subcategories include increasing patient awareness, culturizing prescription, and rational drug use, confidentiality and privacy, and pharmacist-patient relationship/communication, which were the main ethical challenges in the area of drug supply at pharmacies. Conclusions According to a principle-based approach, the greatest challenges were related to two principles of autonomy and beneficence. The policymakers in the healthcare system should emphasize patient independence, patient privacy, and patient-centered services. The results of this study can be used as a tool to introduce ethical challenges to policymakers and develop educational contents, the chart of professional ethics in pharmacies, and accreditation measures of pharmacies.